Chromosome-wide analysis of gene function by RNA interference in the african trypanosome. - Subramaniam, C; Veazey, P; Redmond, S; Hayes-Sinclair, J; Chambers, E; Carrington, M; Gull, K; Matthews, K; Horn, D; Field, M (2006)
Trypanosomatids of the order Kinetoplastida are major contributors to global disease and morbidity, and understanding their basic biology coupled with the development of new drug targets represents a critical need. Additionally, trypanosomes are among the more accessible divergent eukaryote experimental systems. The genome of Trypanosoma brucei contains 8,131 predicted open reading frames (ORFs), of which over half have no known homologues beyond the Kinetoplastida and a substantial number of others are poorly defined by in silico analysis. Thus, a major challenge following completion of the T. brucei genome sequence is to obtain functional data for all trypanosome ORFs. As T. brucei is more experimentally tractable than the related Trypanosoma cruzi and Leishmania spp. and shares >75% of their genes, functional analysis of T. brucei has the potential to inform a range of parasite biology. Here, we report methods for systematic mRNA ablation by RNA interference (RNAi) and for phenotypic analysis, together with online data dissemination. This represents the first systematic analysis of gene function in a parasitic organism. In total, 210 genes have been targeted in the bloodstream form parasite, representing an essentially complete phenotypic catalogue of chromosome I together with a validation set. Over 30% of the chromosome I genes generated a phenotype when targeted by RNAi; most commonly, this affected cell growth, viability, and/or cell cycle progression. RNAi against approximately 12% of ORFs was lethal, and an additional 11% had growth defects but retained short-term viability in culture. Although we found no evidence for clustering or a bias towards widely evolutionarily conserved genes within the essential ORF cohort, the putative chromosome I centromere is adjacent to a domain containing genes with no associated phenotype. Involvement of such a large proportion of genes in robust growth in vitro indicates that a high proportion of the expressed trypanosome genome is required for efficient propagation; many of these gene products represent potential drug targets.